METHODOLOGY FOR STUDYING THE PROBLEM OF WAR AND PEACE IN PERSONAL RELIGIOUS BELIEFS - Z. V. Shwed (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen', 2018)
Purpose. The main purpose of this paper is to consider the methodological peculiarities in the formation and interpretation of war and peace, in the context of the spiritual (irrational) rethinking by humanity and the nature of social phenomena, among which a special place is occupied by the political and legal phenomena of the modern world. This involves solving the following tasks: firstly, to reveal the meaning of modern approaches in understanding the features of religious fundamentalism, and, secondly, to reconstruct the dynamics of transformations in representations of war and peace, in the context of the spiritual practices of the present. Theoretical basis. The author's analysis is based on the systematic reconstruction of modern theoretical models of understanding religious fundamentalism and its connection with the subject of modern anthropological research. The resulted fact that the taxonomy of different types of religious fundamentalism includes more political, legal and economic markers does not provide an answer to the question of what the qualitative influence of the fundamentalist ideas is on the spiritual component of a person's life. Appealing to the problem of religious fundamentalism, in the context of rethinking the phenomena of war and peace, is associated with the actualization of these phenomena in the communicational, media and ideological spheres. That is why, in the context of this analysis, we take into account the main modern approaches in the provisions of religious traditions. These articulate the problems of threat to the global world in the context of actualization and return of the religious factor into the everyday life of a person, including through politics. Originality. The author proves that when analyzing the religious aspect in the reinterpretation of ideas about war and peace, it is necessary to consider, as a doctrinal component, certain types of religious belief doctrines, as well as the individual psychological peculiarities of man. These peculiarities, which are manifested in different types of beliefs, can be verified by the clues in the analysis of religious practices, which represent the meaningful components of the religious doctrine. Conclusions. The reasons for forming ideas about war and peace in theistic religions are a number of provisions related to the nature of the world and of man. They are the result of the manifestation of the act of the Supernatural Essence. In the tradition of rethinking the vocation of man in the context of fundamentalist discourse, these ideas acquire the status of spiritually determined and politically achievable goals. These are conceived in connection with the establishment of the Divine Plan, and they overcome the gap between the material world and the ideal world order.